Comportamentos de saúde e doença numa comunidade Cabo-Verdiana em Lisboa Health and illness behaviors in a Cape Verdean community in Lisbon - Bárbara Bäckström (Universidade de São Paulo, 2011)
O objetivo foi compreender como os indivíduos se comportam em termos de saúde e o que fazem em caso de doença. Análise comparativa realçou semelhanças e divergências de práticas de saúde ou em caso de doença. O estudo foi efetuado numa amostra de 40 cabo-verdianos da primeira geração residentes na região de Lisboa, dividida em subgrupos: grupo social, geração e genero. Baseou-se em metodologia qualitativa com entrevistas semi-estruturadas. As práticas analisadas foram agrupadas em preventivas e de saúde, práticas utilizadas em episódios de doença, recursos para prevenção e tratamento, utilização de remédios caseiros e outros recursos ou terapeutas. Indivíduos experimentaram, ao nível das práticas, três sistemas de saúde que coexistiam em Cabo Verde, oficial, popular e tradicional e o recurso à religião. O discurso acerca das práticas de saúde e de doença demonstrou existirem diferenças, em alguns aspectos, entre grupos sociais e entre generos e gerações. Práticas de saúde destes imigrantes são idênticas às dos portugueses em contextos socioeconomicos semelhantes. Resultados sugerem existência de diferenças entre grupos sociais relativamente às práticas, na esfera da saúde e da doença. Mais que cultura e etnicidade, que se moldam às condições materiais de existência, neste estudo, o nível socioeconomico determinou as maiores diferenças a interferir nas práticas de saúde e doença, de grupo com cultura de base comum. Em geral, os indivíduos sobrevalorizaram sua identidade étnica e cultura de origem. Pertencimento a grupos sociais diferentes dá origem a partilha do sentimento de pertença cultural, mas não a comportamentos e práticas idênticos. This study aims at analysing, through personal reports, the way individuals behave in terms of health and illness. A comparative analysis of the collected data was performed, with the purpose of highlighting divergences in the health and illness practices. The study was undertaken with a sample of 40 «first generation» Cape Verdeans living in the Metropolitan area of Lisbon, divided into distinct groups: social (popular and elite), generation (younger and older) and gender (men and women). A qualitative methodology was employed, by conducting semi-structured interviews for the collection of information. The health and illness practices were grouped into preventive and health care practices, practices used in episodes of illness, resources used for prevention and treatment, use of home remedies, and other alternative resources. Individuals who are part of our study experimented, at the level of practices, with the three health systems that existed in Cape Verde, namely, the official, popular and traditional, and recourse to religion. The discourse analysis concerning health and disease practices showed there are differences, in some respects, between social groups. There were also slight differences between genders and generations. These immigrants' health practices are identical to those of the Portuguese who are in similar socioeconomic contexts, with no significant effects of immigration itself on these practices. The analysis of the results confirms the existence of differences between social groups concerning the health and illness practices. They were more determined by the socioeconomic factors than by the cultural and ethnic aspects. Those differences also highlighted the existence of a unifying aspect, resulting from their cultural heritage. Although belonging to different social groups, the existence of a common culture and ethnic identity originates a shared feeling of cultural belonging, but not identical behaviours and practices.